2008
DOI: 10.1243/09544100jaero280
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady aerodynamic effects experienced by aerofoils during acceleration and retardation

Abstract: This investigation focuses on the aerodynamic effects caused by acceleration and retardation. It shows that, when an object is accelerated in a compressible fluid, the aerodynamic forces and moments experienced by the object at any instantaneous Mach number are different to those, experienced at the same Mach number, when the object moves at constant velocity. A supersonic biconvex aerofoil was chosen, with Fluent as the computational fluid dynamic (CFD) software. Constant velocity (steady state) simulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It was then demonstrated that drag on an axisymmetric flare missile dropped by 20% in comparison with steady values if the flare geometry was accelerated through the transonic range at 4 500 ms -1 . Roohani and Skews have conducted detailed studies of the unsteady aerodynamics of accelerating bodies, such as aerofoils [40][41][42][43][44] and axisymmetric objects [45] undergoing unidirectional acceleration through the subsonic and transonic ranges. This was modelled numerically using source terms added to the momentum and energy equations in the code FLUENT [46].Shock wave boundary layer interaction was found to have significant effect on the shock wave position and strength in the transonic range.…”
Section: Earlier Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It was then demonstrated that drag on an axisymmetric flare missile dropped by 20% in comparison with steady values if the flare geometry was accelerated through the transonic range at 4 500 ms -1 . Roohani and Skews have conducted detailed studies of the unsteady aerodynamics of accelerating bodies, such as aerofoils [40][41][42][43][44] and axisymmetric objects [45] undergoing unidirectional acceleration through the subsonic and transonic ranges. This was modelled numerically using source terms added to the momentum and energy equations in the code FLUENT [46].Shock wave boundary layer interaction was found to have significant effect on the shock wave position and strength in the transonic range.…”
Section: Earlier Workmentioning
confidence: 99%
“…At this point it is important to explain the concept of flow history as used in the present context [43]. When an object is accelerated in a compressible fluid, the unsteady flow field generated is not allowed sufficient time to reach equilibrium at any specific Mach number.…”
Section: Earlier Workmentioning
confidence: 99%
See 1 more Smart Citation